Birth rites and rights - Ebtehaj, Fatemeh (Oxford : Hart Publishing, 2011)
'This multi-disciplinary collection of essays from the Cambridge Socio-Legal Group is concerned with the varying circumstances, manner, timing and experiences of birth. It contains essays from a wide range of disciplines including law, medicine, anthropology, history and sociology, examining birth from the perspectives of mother, doctor, midwife and father. Questions considered in the book include: who has power during the birthing process? How has the experience of birth changed over time? Should birth mark a significant change in the legal status of the foetus? What is the proper role of birth registration? What role, if any, do fathers have in the birthing process? What legal rights should the woman have to refuse treatment during the birthing process? What is the significance of changes of the age at which women give birth? This stimulating collection of papers provides new insights into one of life's most momentous moments'--Provided by publisher.
Becoming a mother : continuities and discontinuities over three decades / Ann Oakley, Meg Wiggins, Vicki Strange, Mary Sawtell, and Helen Austerberry -- Changing medical birth rites in Britain 1970-2010 / Francoise Barbira Freedman -- Are doctors still improving childbirth? / Susan Bewley and Lin Foo -- Midwife-mother relationship / Mavis Kirkham -- Loneliness of status : the legal and moral significance of birth / Jonathan Herring -- Refusing medical treatment during pregnancy and birth : ethical and legal issues / Rosamund Scott -- Consequences for preterm infants of antenatal glucocorticoid treatment / Alison Forhead and Abigail Fowden -- Fathers, birth and law / Richard Collier -- Recording births : from the reformation to the Welfare Reform Act / Rebecca Probert -- Changing form of birth registration / Julie McCandless -- Birthright had nothing to do with it : royal inheritance in the Middle Ages / Francis Woodman -- Infanticide and insanity in 19th century England / Shelley Day Sclater -- Explaining the trend towards older first time mothers : a life course perspective / Irenee Daly -- Too late or too many : dilemmas facing the modern woman seeking help with fertility / Peter Braude and Tarek El-Toukhy -- IVF birth data presentation : its impact on clinical practice and patient choice / Emily Jackson and Hossam Abdalla.
Includes bibliographical references and index.
Keywords: Childbirth -- Law and legislation; Childbirth -- Social aspects; Childbirth -- Health aspects